Pemberdayaan Kewirausahaan Santri guna Meningkatkan Ekonomi di Pondok Pesantren Al- Qur’an Syifaul Furqon Kecamatan Ciawi Kabupaten Bogor - Muhammad Ishak; Kholifatul Husna Asri (ALIF, 2022)
Islamic Boarding Schoolentrepreneurship. This is one of the efforts to reduce the unemployment rate. The method used is a qualitative approach, with data collection techniques through observation, interviews and documentation. The results showed that entrepreneurship education carried out in Islamic boarding schools was very important to be given to students, this was as a provision of knowledge and skills of students. In practice, Islamic boarding schools seek to improve the abilities of students through empowerment programs. This program is an effort in addition to training and developing children's talents, in entrepreneurship there are also character values ??that can educate students to become students with good character. The implementation of empowerment developed through entrepreneurship is also said to be a strategy in forming an attitude of independence. This attitude is a provision that must be possessed by students when they face the world outside the pesantren.